Design of composite insulation panels containing 100% recycled cotton fibers and polyethylene/polypropylene packaging wastes. (1st July 2021) - Sezgin, Hande; Kucukali-Ozturk, Merve; Berkalp, Omer Berk; Yalcin-Enis, Ipek
Abstract: The aim of this study is to produce high value-added composite materials by combining textile and packaging waste from two different sectors. Waste denim fabric was used as the reinforcement material, while polypropylene and polyethylene bottle caps, food, and cleaning containers were used as the matrix material for the production of composite panels. These composite panels were investigated in terms of air permeability and thermal and acoustic insulation behavior. The results indicate that the developed textile-based composite panels are applicable as commercial support materials and offer improved thermal and acoustic insulation properties. The developed composite material provides sound transmission loss up to 8 dB, and improves the thermal resistance value up to 0.11 m 2o C/W. On the other hand, the flame retardant property of this composite material should be tested and developed at the point of applicability as an insulation material.